Effect of prior exercise on the VO2/work rate relationship during incremental and constant work rate exercise - Marles, A.; Mucci, P.; Betbeder, D.; Prieur, F. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
A disproportionate increase in VO2 ("VO2 excess") has been reported at elevated intensity during incremental exercise (IE) (Zoladz, Duda et al. 1998). This phenomenon could have the same origin than the VO2 slow component observed during heavy constant work rate exercise (CWRE). It has also been demonstrated that heavy exercise could diminish the VO2 slow component (Gerbino, Ward et al. 1996). In this context, the aim of this study was to evaluate whether prior heavy exercise alter the"VO2 excess" as it alters the amplitude of the VO2 slow component. Methods Ten subjects (trained in sprint) performed three tests (T1, T2, T3) on a cycle ergometer: T1 was a IE; T2 was composed of a CWRE (90% of VO2max) followed by six minutes at 35 W and by a IE and T3 was composed of two CWRE separated by six minutes of exercise at 35 W. The slope and the intercept of each individual VO2/Work rate relationship was calculated with a linear regression using data before the first Ventilatory Threshold (pre-VT1 slope). Then the expected VO2max (VO2maxexpected) at Pmax was calculated using the pre-VT1 slope and intercept. The "VO2 excess" was assessed by the difference between VO2maxmeasured and VO2maxexpected. During T3, the magnitude of the VO2 slow component was evaluated by the difference between VO2 at the fifth minute and VO2 at the third minute of each CWRE (Delta VO2(5`-3`)). Results VO2maxmeasured was significantly higher than VO2maxexpected during IE of T1 and T2. "VO2 excess" during IE was not different between T1 and T2 (+259 ± 229 ml.min-1 vs +222 ± 221 ml.min-1). During T3, delta VO2(5'-3 ') was significantly decreased during the second CWRE (338 ± 65 ml.min-1 vs 68 ± 98 ml.min-1). Discussion/Conclusion These results confirm the existence of a "VO2 excess" at elevated intensity during IE because VO2maxmeasured was higher than VO2maxexpected. The amplitude of the "VO2 excess" during IE was however not affected by a prior exercise whereas the slow component of VO2 evaluated by Delta VO2(5'-3 ') during CWRE was lowered. This implies that prior exercise did not have the same effects on the slow component of VO2 than on the "VO2 excess". This study failed to establish a relationship between the"VO2 excess" phenomenon during IE and the slow component of VO2 during CWRE.